FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON-KEUANGAN DI INDONESIA - Ardani, Fitri Azzahwa; Chandra, Santoso (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Earnings management is management's action in making several changes to external financial statements, both in terms of accounting treatment, economic decisions, or other accounting methods in order to present financial statements in a different way (higher or lower income value). The purpose of this study was to obtain empirical evidence regarding the effect of firm size, leverage, firm age, audit quality, free cash flow, proportion of independent commissioners, profitability, board of directors, and managerial ownership on earnings management as the dependent variable. The population of this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) with a research period of 2018-2020. The sample used in this study amounted to 103 companies with 309 data obtained from data collection techniques in the form of purposive sampling. The hypothesis testing method used in this study is the multiple regression method. The results of this study found that firm age, audit quality, and free cash flow have a negative effect on earnings management, while profitability has a positive effect on earnings management. The other four variables, namely firm size, leverage, proportion of independent commissioners, board of directors and managerial ownership have no effect on earnings management.